A cross-sectional survey of attitudes towards education in implant dentistry in the undergraduate dental curriculum - Ramona Schweyen; Bilal Al-Nawas; Christin Arnold; Jeremias Hey (SpringerOpen, 2020)
Abstract Background An ongoing debate in dental education is whether implant dentistry, as a multidisciplinary domain, should be integrated into the undergraduate curriculum. The aim of the present study was to evaluate the perspectives of novices, clinical educators, and experienced dentists with regard to the importance of theoretical and practical implant dentistry teaching content in undergraduate dental education. The specific objective was to determine whether a consensus could be found concerning aspects of theoretical knowledge, implant position planning, implantation, prosthetic treatment procedures, postoperative care, and prerequisite experiences that should be provided in undergraduate dental education. Results A positive consensus existed in terms of theoretical education, assistance in surgical and prosthodontic procedures, implant planning and restoration in straightforward cases (i.e., posterior single crowns and bridges, overdentures on nonconnected implants), and postoperative care. A negative consensus existed for bone augmentation. Implantation was supported by novices (i.e., students and graduates). In addition, more experienced dentists were more likely to oppose implantation performed by undergraduates. The most preferred implantation method was implant insertion using a digitally fabricated drilling template, after surgical flap elevation. Conclusions Students and graduates preferred a comprehensive undergraduate education that included implant dentistry. Dentists working in private practice, and especially dentists working as university educators, were critical towards the integration of implant-related learning content into undergraduate education. The intention of medical education is to impart knowledge to students and to prepare them for life-long learning and continual professional development after graduation. Thus, an undergraduate dental curriculum that provides students a solid introduction and knowledge foundation in implant dentistry is recommended.